Morphological Analysis of Medical Terminology in Conference Abstracts for ESP Reference - Sherly Arwinda; Muhammad Rizky Rochmawan (Universitas Pahlawan Tuanku Tambusai, 2026)
Mastery of medical terminology is a crucial competency in international scientific communication, especially in abstract writing that demands high information density. However, many health academics still face challenges in utilizing the productivity of affixation to build precise medical terms. This study aims to identify the morphological structure of medical terms, compare their frequency of occurrence, and formulate pedagogical references for teaching English for Specific Purposes (ESP). This descriptive qualitative study uses content analysis method on a data corpus consisting of abstracts of International Conference on Health Practice and Research (ICHPR) in 2024 and 2025. Medical terms are dissected based on word-building theory to identify patterns of prefixes, roots, and suffixes. The analysis involves multi-step coding process where terms are validated against medical lexicons to ensure accuracy in identifying the derivatives. The findings show the dominance of the terms Hypertension (39 times) and Tuberculosis (15 times) as a consistent research focus. A shift in terminology trends from mental health issues (such as Schizophrenia) in 2024 to chronic physical issues (such as Pulmonary and Myofascial) in 2025 was also identified. The productivity patterns of derivational suffixes (such as -al, -ary, -ic) and pathological affixes (such as -itis, -osis) were proven to be the main instruments in the condensation of clinical meaning. Pedagogically, these results provide a reference list of priority vocabulary based on a real corpus that English lecturers can use to increase the morphological awareness of health students in facing global publications.